Russian pogroms and Jewish revolution, 1905 class, ethnicity, autocracy in the first Russian Revolution - Surh, Gerald D. 1939- (Routledge studies in the history of Russia & Eastern Europe, 2024)
"This book, based on extensive original research, examines the widespread and violent pogroms against Jews which took place in the Russian Empire in 1905. It briefly surveys the earlier history of Jews in the Russian Empire and the discriminatory policies against them. The work outlines the extent of the killings and lootings in 1905, explores the role of the authorities who were often neutral or complicit in the violence, and highlights Jewish self-defense measures. It relates the pogroms to the place of the Jews in Russian urban and rural life, to social change and modernisation, and to the revolutionary events of 1905, in which Jews played a prominent role, and during which calls for ethnic self-determination arose among many nationalities of the Russian Empire, most broadly and consequentially among Jews. Overall, the book views the pogroms as a consequence not only of Russian antisemitism, but of the broader, revolutionary breakdown of Russian state and society in 1905"--